IMPROVING THE INTEGRATION OF SCIENCES IN EDUCATION OPPORTUNITIES - Inoyat ELMURODOVA (Scholar Express Journal, 2024)
In this article, the improvement of interdisciplinary integration in education, the realization of acquired knowledge and skills of elementary school students in the content of interdisciplinary integration, the understanding of the essence of the existence in nature, the processes and events that take place in them, this study The problems of forming a scientific worldview in students by comprehensively imagining general and specific concepts in the content of science, and applying them to practice are highlighted. Also, the process of improving the interdisciplinary integration in primary education is covered.
Keywords: Integration; School; Education; Learner